The effect of preoperative hypoalbuminemia on complications after primary hip arthroplasty - Yang Tan; Lingxiao Jiang; Hankun Liu; Zhengqi Pan; Hua Wang; Liaobin Chen (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Objectives To explore the risk factors of preoperative hypoalbuminemia and its’ effects on complications in the elderly with primary hip arthroplasty. Methods A total of 211 elderly inpatients who underwent hip arthroplasty were collected. All patients were divided into the control group (preoperative serum albumin ≥35 g/L) and case group (preoperative serum albumin <35 g/L). The risk factors of preoperative hypoalbuminemia and the postoperative complications were analyzed. Results Compared to controls, hypoalbuminemia patients were older (P = 0.026), had lower BMI (P = 0.045), higher cardiac function score (P < 0.0001), higher ASA scores (P = 0.023), and longer hospital stay (P < 0.001). The intraoperative albumin loss in the case group was significantly higher than that of in control group (P < 0.001), but there was no significant difference in operation time and intraoperative blood loss between the two groups (P >0.05). Compared to controls, hypoalbuminemia patients had a higher risk for any complication (P = 0.014), such as delayed wound healing, pleural effusion, and pneumonia. The risk of postoperative complications increased by 6.9% with every 1 year old is increasing (age > 60). The risk of postoperative complications in the case group was 1.89 times higher than that in the control group. Conclusion Patients with older age, poor nutritional status, and more than 2 concomitant diseases are more likely to develop preoperative hypoalbuminemia. Preoperative hypoalbuminemia is related to the increased incidence of postoperative complications. Perioperative albumin loss is not only due to perioperative blood loss, but also related to vascular permeability and abnormal albumin metabolism.